Surface marker cluster translation, rotation, scaling and deformation: Their contribution to soft tissue artefact and impact on knee joint kinematics - Benoit, D.L.; Damsgaard, M.; Andersen, M.S. (Journal of biomechanics, 2015)
When recording human movement with stereophotogrammetry, skin deformation and displacement (soft tissue artefact; STA) inhibits surface markers’ ability to validly represent the movement of the underlying bone. To resolve this issue, the components of marker motions which contribute to STA must be understood. The purpose of this study is to describe and quantify which components of this marker motion (cluster translation, rotation, scaling and deformation) contribute to STA during the stance phase of walking, a cutting manoeuvre, and one-legged hops. In vivo bone pin-based tibio-femoral kinematics of six healthy subjects were used to study skin marker-based STA. To quantify how total cluster translation, rotation, scaling and deformation contribute to STA, a resizable and deformable cluster model was constructed. STA was found to be greater in the thigh than the shank during all three movements. We found that the non-rigid (i.e. scaling and deformation) movements contribute very little to the overall amount of error, rendering surface marker optimisation methods aimed at minimising this component superfluous. The results of the current study indicate that procedures designed to account for cluster translation and rotation during human movement are required to correctly represent the motion of body segments, however reducing marker cluster scaling and deformation will have little effect on STA.